A critical analysis of the Role of Social Media in Shaping National Well-Being - Cristina Dinescu (Journal of Social Science, 2023)
Through its impact on a variety of societal factors, such as personal psychological health (PH), community involvement, political debate, and social connection, social media significantly shapes national well-being. Evaluating social media's influence on molding national well-being is essential for resolving its impacts and optimizing its advantages, despite the fact that it may have both good and bad consequences. This research investigates the relationship between adolescents’ psychological health (PH) and social media utilization. The information was collected over the course of several years as part of a research project known as "The Korean Youth Panel Survey (KYPS)." It is anticipated that hierarchical linear models (HL) will be used to investigate the psychological effects of using the Internet. The analysis demonstrates that social media usage on the internet has a negative correlation with students' mentalwell-being as indicated by self-expressed psychological health issues and thoughts of suicide (TOS) while retaining steady “a variety of time-lagged control factors at the individual (student) and contextual (school) levels." Since much prior research on the benefits and drawbacks of using digital social media relies on cross-sectional information, causal inference is not possible. This study provides more convincing proof of the direction of causality by employing longitudinal information.